Understanding Dynamic Collaboration in Teleconsultation. Issue 1 (2nd January 2016) - Yan, Ziyu; Guo, Xitong; Vogel, Douglas R.
Abstract : Information and communication technology has been widely deployed in the provision of healthcare for decades. Teleconsultation, one of the new means of providing healthcare solutions, has been prevalently implemented in numerous countries. In principle, it is expected with great potential to improve the effectiveness and efficiency of healthcare service through wide accessibility and cost control. However, many teleconsultation systems have been installed but abandoned rapidly or used at a disappointing low level. This paper explores the antecedents of low usage in post-adoption of teleconsultation service in clinical practice. We identify specific theoretical attributes targeted on the research problem and extend the Technology–Organization–Environment (TOE) framework into a multi-dimensional analytical framework. We design a comparative case study and conduct deductive analysis to test our propositions using data from multiple sources. The proposed analytical framework and empirical findings not only provide theoretical contribution by articulating the TOE framework to reflect the specific and distinguished characteristics in teleconsultation services, but also provide implications for practitioners to develop better strategies for teleconsultation collaboration.